Uptake and distribution of Na+ in rice genotypes under salinity condition - Sultana, MA; Hossain, MA; Tareq, MZ; Sarker, MDH; Mojakkir, AM; Fakir, MSA (SAARC Journal of Agriculture, 2016)
Abstract not available SAARC J. Agri., 14(1): 141-144 (2016)